The effect of McConnell taping on knee biomechanics : what is the evidence? - Leibbrandt, Dominique Claire; Louw, Quinette (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.